KARAKTERISTIK BUDAYA KOMUNIKASI POLITIK ELITE MUHAMMADIYAH - Pia Khoirotun Nisa (Al Amin: Jurnal Kajian Ilmu dan Budaya Islam, 2018)
Muhammadiyah is one of the elements from the public room of Indonesia, it accepts amount of political policies from the power of nation and responses them as the tradition of its organization. The special characteristic of organization determines political communication that is used. In doing political communication, the political elite of Muhammadiyah has to be able to play very important role in a political system because it becomes determined part from the process of political socialization, political culture, political participation and political recruitment.